INTERNATIONAL SCENARIO OF CYBERCRIME AGAINST WOMEN IT'S EVOLUTION AND EFFECTS ON PERSONAL LIFE - Vaishnav, Abhilasha; Dewan, Beena (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Over the recent years, Cyber-Crime has become one of the major concerns of the world. However, India deserves special focus in this context as it has one of the highest rates of cyber-crime in the world. Indian women are the most likely demographic of the country who are likely to affected by these types of crimes. It describes the origin of cyber-crimes, and the way women are most likely to be the victims of these types of crimes. Since, special focus has been put on India, the cyber-laws, and their loopholes have also been addressed. In addition to that, also addresses the gaps that exist between legal actions, and advancements in technology. Lastly, several cases related to cyber-crimes, and the laws that were implemented during those cases have also been discussed. Discussion is also made about relationship between women, and cyber-crimes in an international perspective. Several reports and articles have elucidated the fact that the condition of women affected by cyber-crimes is very similar to that of women in India. This situation has taken negative turn ever since the global lockdown. This case is even worst in the case of countries located in the Middle East, and other developing countries. In the significance of overseas law and cyber-crime related law is been discussed. The impact of these laws in mentioning the security of women is also discussed.